1995
DOI: 10.1097/00004714-199508000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Response to Desipramine in Dysthymia

Abstract: Little is known about factors that may predict the response of dysthymia or other forms of chronic depression to treatment with antidepressant medication. We investigated several sociodemographic and clinical variables for their relationship to the acute treatment response to desipramine in subjects with DSM-III-R dysthymia. Subjects with DSM-III-R dysthymia were treated with desipramine in an open fashion for 10 weeks. Various clinical and sociodemographic variables were assessed at baseline. Ratings of depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…With a rare exception (17), no adequately powered previous studies have searched for baseline features predicting which patients will achieve remission as opposed to those who will respond to treatment. Response moderator studies with small samples have yielded inconsistent correlates of response (18), except for pretreatment depressive symptom severity, which has been associated consistently with lower response rates (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Therefore, STAR*D also aimed to evaluate moderators of symptom remission.…”
Section: Methodmentioning
confidence: 99%
“…With a rare exception (17), no adequately powered previous studies have searched for baseline features predicting which patients will achieve remission as opposed to those who will respond to treatment. Response moderator studies with small samples have yielded inconsistent correlates of response (18), except for pretreatment depressive symptom severity, which has been associated consistently with lower response rates (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Therefore, STAR*D also aimed to evaluate moderators of symptom remission.…”
Section: Methodmentioning
confidence: 99%
“…22,159,[193][194][195] Studies that focused on social and interpersonal impairments likewise indicated marked deficits among dysthymic patients. 22,159,193,[196][197][198][199] These reports indicated that social impairment correlated positively with increasing severity and chronicity of the illness, and worsened with onset of double depression. In addition to alleviating the depressive symptoms, antidepressants attenuated the social impairment characteristic of dysthymic patients.…”
Section: Psychosocial Factors and Stressors In Major Depressive Disormentioning
confidence: 99%
“…Thus, it was posited that the reduced capacity to enjoy leisure time may be a state marker of chronic depression. 131,159,201 It is interesting that while significant improvement in quality of life was observed among dysthymic patients treated with either imipramine or sertraline over 12 weeks, 202 self-reported social functioning showed greater improvement than did participation in leisure activity. It was suggested that the delayed alleviation of certain aspects of psychosocial functioning may have been due to the relatively short duration of pharmacotherapy relative to the patients' often life-long impairment.…”
Section: Psychosocial Factors and Stressors In Major Depressive Disormentioning
confidence: 99%
“…On the other hand, social support may positively influence drug response [65], as can family support [66], and perceived criticism by spouses can trigger relapses even in patients receiving continued treatment [66]. Recent data from a large antidepressant trial has found that socioeconomic variables -low education, lower income and unemployment -are robust predictors of a poor response to the SSRI citalopram [67]; it is unknown if these effects are themselves mediated through exposure to stressful life events or lack of support systems.…”
Section: Depressive Disordersmentioning
confidence: 99%